Anthropology and Metaphysics in Kant’s Categorical Concept of Law: An interpretation of paragraphs B and C of the Legal Theory - Höffe, Otfried (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
Kant searches for the ground of the obligation of moral rules in the field of the pure reason concepts, aiming at a categorical imperative free from empirical contents. This paper challenges this process emphasizing the importance of the anthropological, empirical elements in Kant´s moral philosophy, without affecting the core of his philosophy. To that end, we make a fundamental distinction between moral theory and moral itself. The result is an understanding of moral in which the requirement to have a metaphysically founding to win an a priori pattern doesn´t exclude the anthropological elements, but they rather appear as indispensables.
Keywords: Ethic; moral; law; categorical imperative; a priori